Mondialisation des engagements d’Équité, Diversité et Inclusion à l’université et intégration d’une posture anti-raciste dans un cursus de français L2 - Gaëlle Planchenault (Recherches en didactique des langues et des cultures)
In recent years, faculty members have heard numerous calls to review their research, teaching and administrative practices from the perspective of a mission known as Equity, Diversity, Inclusion, or under the acronym EDI, to which the terms Decolonization and Social Justice are sometimes associated. These calls have found a varying support depending on the disciplines, institutions and countries, where teachers and researchers have undertaken to integrate these objectives into their work. In Canada, following the report of the Truth and Reconciliation Commission (2015), universities developed initiatives which claimed to decolonize and indigenize the curriculum. This article questions the impact of a higher education course, which studied the media coverage of racialized activists in France, as taught in this context. After a brief presentation of the institutional use of the word 'decolonization' and its critiques, the article describes the parameters of the development of this course and its implications in terms of engagement and allyship. It then questions the dimension of the latter considering that the course is taught in L2 French, a language whose presence around the world finds its origins in a colonial and imperialist history and in the discrimination of indigenous, creole, regional and vernacular languages. Finally, I present the argument that positionality is a crucial part of the decolonial reflection and the critical and anti-racist pedagogy, for which epistemological points of view must be openly presented and historicized.